Economics of Low-Rise Steel-Framed Structures - Ruddy, John L. (Engineering Journal, 1983)
The structural engineers input at the conceptual state of a project is his most important contribution. The purpose of this early effort is to determine the materials of construction, and to establish the system which is to use these materials. Inadvertently, these early decisions establish the lower boundary of the economies that can be realized as design progresses. Options available to the engineer are numerous. In addition to the multiple framing options, within the constraints of each option, there are a multitude of permutations of elements which further magnify the options. Confidence that a true optimum solution has been realized seldom exists. The magnitude of the problem certainly does not diminish its importance. Our purpose here is to investigate the structural economic considerations of a one-story framing system in the interest of predicting the optimum bay dimensions. The objective of the investigation is to realize least cost. Least cost is not synonymous with the least weight of the structural steel elements employed. In fact, a least weight approach does not consider all of the structural elements which influence the bay size. Foundation considerations may significantly effect results. An emphasis on cost has the consequence of introducing very subjective elements into the analysis process. The material and labor costs vary from supplier to supplier within a geographic region, and certainly among suppliers or subcontractors nationally. The approach is rational, yet it is intimately tied to those unit costs tabulated in Table 1.